Factors Affecting Financial Satisfaction of Uttaradit Rajabhat University Personnel - Ratanasongtham, Worapan; Chitmun, Suphansa; Jankawee, Tulaporn; Duangtanoi, Waritsara (Journal of Industrial Business Administration, 2023)
The aim of this research is to study the impact of financial literacy, financial attitudes on financial behavior, and financial satisfaction of personnel at Uttaradit Rajabhat University.The sample groups of this study included 187 people from Uttaradit Rajabhat University personnel. The research instrument was a questionnaire and the statistics for data analysis, including mean, standard deviation, correlation analysis, and complex regression analysis for the hypothesis test. The results indicated that financial literacy and financial attitudes showed a positive impact on financial behavior and financial satisfaction. In addition, financial behavior also has a positive impact on financial satisfaction. Therefore, the personnel at Uttaradit Rajabhat University should pay more attention to basic financial knowledge education and have an accurate understanding of financial analysis principles and also a good financial attitude. This method was one of the guidelines for the development of personal financial behavior in order to achieve more satisfaction in their own financial status.